Front Military Rule to Civilian Administration: Consequences ofAbuse of Power in Nigéria - Odorige, Frederick Omoyoma (Dunakavics, 2023)
Olusegun Obasanjo was sitting president in Nigéria when over two hundred, mostly civilian citizens were killed in a reprisal attack by the Nigérián military because security officers were reportedly killed by agitators and militia gangs in these two communities, Odi and Zaki Biam in 1999 and 2001 respectively. Alsó, between January 2017 and January 2023, under suspicious circumstances, the Nigéria Air Force „mistakenly” bombed and killed innocent Nigerians sixteen times during the administration of President Muhammadu Buhari. Both were leaders who transformed from the military intő civilian administrations. They both ruled Nigéria under the force of militia through undemocratic means. Both leaders were retired army generals who later ruled Nigéria as civilian presidents. The grave consequences of abuse of power, perpetuated by both, leading to the deprivation of the funda- mental rights to life of the victims are the subject matter of this paper. I have drawn the trajectories of these events using qualitative content analysis based on comparative perspec- tives. The result shows the need fór a demilitarization process fór previous leaders of military rule before seeking political office. Nigéria must address these issues strategically so that leaders can deal with issues through clear political means to combat terrorism. Alsó, the need to address the welfare needs of serving military personnel within the force and improve work conditions is addressed.